The Influence Of Workload And Organizational Climate On Turnover Intention Through Job Stress As An Intervening Variable In Sales Employees Of Auto 2000 Medan-Binjai - Daud Arifin (International Journal of Economics and Management Research, 2023)
The purpose of this study was to determine the effect of workload and organizational climate on turnover intention through job stress as an intervening variable in Auto 2000 Medan-Binjai Sales employees. This research is a type of associative research with data analysis techniques using path analysis with SmartPLS software. The data collection technique used in this research is a questionnaire. The results showed that workload has a significant positive effect on job stress in Sales Auto 2000 Medan-Binjai employees, organizational climate has a negative and insignificant effect on job stress in Sales Auto 2000 Medan-Binjai employees. Workload has a significant positive effect on turnover intention of Sales Auto 2000 Medan-Binjai employees. Organizational climate has a negative and insignificant effect on turnover intention of Sales Auto 2000 Medan-Binjai employees. Job stress has a significant positive effect on employee turnover intention of Sales Auto 2000 Medan-Binjai. Workload has a significant positive effect on turnover intention mediated by job stress in Sales Auto 2000 Medan-Binjai employees. Organizational climate has a negative and insignificant effect on turnover intention mediated by job stress in Sales Auto 2000 Medan-Binjai employees.